Study on the Satisfaction Level of Lecturers and Educational Staff Towards the Quality of Remuneration Services Using the Service Quality Model at Muhammadiyah University Sorong - Rawi, Rais Dera Pua; Lewenussa, Ramli; Setiawan, Hendra (Universitas Muhammadiyah Ponorogo, 2025)
The purpose of this research is to analyze the factors that influence the quality of remuneration services for educators and educational staff at Universitas Muhammadiyah Sorong as a BLU and to analyze the impact of the quality of remuneration services on the satisfaction levels of educators and educational staff at Universitas Muhammadiyah Sorong as a BLU. The research method used is a survey with statistical testing. The sample used consists of the Implementing Elements and Academic Supporting Elements of Universitas Muhammadiyah Sorong, which represent all users of services at Universitas Muhammadiyah Sorong. Data analysis uses the Importance-Performance Analysis method. The research results show that all dimensions of remuneration service quality (tangible evidence, assurance, responsiveness, and reliability) have a positive and significant impact on satisfaction levels, except for the empathy dimension, which does not have a significant impact. The increase in satisfaction is more driven by the quick responsiveness of the remuneration service, followed by tangible evidence, reliability, and assurance. The implication for Muhammadiyah University of Sorong is the need to prioritize improvements in these dimensions in an effort to enhance the satisfaction of lecturers and educational staff through the provision of optimal remuneration services.